2007
DOI: 10.1007/s00592-007-0257-3
|View full text |Cite
|
Sign up to set email alerts
|

Induction of hyperglycaemia in zebrafish (Danio rerio) leads to morphological changes in the retina

Abstract: Diabetes affects over 16 million Americans yearly, resulting in hyperglycaemia and microvascular complications, including retinopathy, neuropathy and nephropathy. Animal models have been developed to examine the immunological aspects of type 1 diabetes and the pathogenic mechanisms associated with diabetic retinopathy, but the methods of diabetes induction raise concerns regarding these models. Zebrafish (Danio rerio) have been used extensively to study developmental processes and mutant zebrafish strains have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
144
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(163 citation statements)
references
References 31 publications
17
144
0
2
Order By: Relevance
“…Zebrafish have similar metabolic regulation of glucose as that found in mice and human, [60] and the Giant Danio is phylogenetically closer to Danio rerio [14]. Effects of induced hyperglycemia stress resulted in positive correlation between the %glucose solution and the cortisol level, as well as the incubation time and the cortisol level as seen previously in other model systems, consistent with onset of adrenal cortex function and steroidogenesis [32]. In conclusion, the present study demonstrated that hyperglycemic effects on adrenal cortex function and steroidogenesis in the freshwater fish Giant Danio Devario aequipinnatus embryos.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Zebrafish have similar metabolic regulation of glucose as that found in mice and human, [60] and the Giant Danio is phylogenetically closer to Danio rerio [14]. Effects of induced hyperglycemia stress resulted in positive correlation between the %glucose solution and the cortisol level, as well as the incubation time and the cortisol level as seen previously in other model systems, consistent with onset of adrenal cortex function and steroidogenesis [32]. In conclusion, the present study demonstrated that hyperglycemic effects on adrenal cortex function and steroidogenesis in the freshwater fish Giant Danio Devario aequipinnatus embryos.…”
Section: Discussionsupporting
confidence: 79%
“…These data demonstrate that hyperglycemia can reliably be produced in the Giant Danio Devario aequipinnatus embryos, as has previously shown in Danio rerio species by [32,40]. The induced hypergylcemia in adult rainbow trout through manipulation of food source and stocking conditions [41].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…IPL and INL layers were shown to be significantly reduced in treated zebrafish, with the thickness of the IPL approximately 55% of the INL. 96 This study provided some support to the idea that zebrafish can be utilized to model DR. This finding was confirmed by another study where visual impairment was evident after inducing hyperglycaemia in zebrafish.…”
Section: Drmentioning
confidence: 90%
“…95 Hyperglycaemic zebrafish are shown to have similar retinal structure abnormalities as seen in diabetic patients. 96 Hyperglycaemia can be induced in adult zebrafish by immersing alternately in glucose solution and water over 28 days followed by retinal examination. IPL and INL layers were shown to be significantly reduced in treated zebrafish, with the thickness of the IPL approximately 55% of the INL.…”
Section: Drmentioning
confidence: 99%